The power of things : enhancing employability in higher education through object-based learning : final report. - Salmon, Fiona; Kevin, Catherine; Wurm, Jackie; Baigent, Michael; Reynolds, Vicki; Sherwin, Fiona; Gaunt, Heather (Australia. Dept of Education and Training (DET), 2019)
We live in an era of disruptive change in which the pace of technological innovation is remarkable. Unprecedented access to information is redefining the ways we live, learn and work. As a university, we must rise to the challenge of preparing our graduates for success in a future that will be every bit as dynamic and unpredictable as it is exciting. This project was conceived as a response to the challenge faced by higher education providers in preparing students for employment success in a rapidly changing world. It was informed by a substantial body of scholarly literature indicating that graduate employability is a significant and ongoing concern for the sector: that despite the efforts of tertiary institutions to help students develop the skills, knowledge and attributes for securing and sustaining work in the short and longer term, there are many graduates emerging from their studies who are not adequately prepared for this task. The project was aligned with the OLT employability skills program priority and led by Flinders University Art Museum (FUAM) as a seed initiative. It was motivated and shaped by emerging knowledge around the pedagogical power of 'object-based learning' (OBL), and its application in tertiary-level contexts to improve the capacity of students to see, think and communicate effectively. The project observed that Australian universities are custodians of rich and vast cultural and scientific collections, historically established as educational tools but now largely under-utilised by academic staff. By bringing these holdings back into the pedagogical frame, through initiatives driven by OBL, the project also sought to address longstanding recommendations of the Australian Vice Chancellors' Committee to 'maximise' the use of university collections in academia, harnessing their potential in the design and delivery of educational experiences (Australian Vice-Chancellors' Committee, University Museums Review Committee, 1996). [Executive summary, ed]